Housing future for ageing in place - Karol, Elizabeth; Spanbroek, Nancy (Australian Housing and Urban Research Institute Southern Research Centre, 2006)
This paper examines how the desire of people to age in their home is being met through the design of new and renovated homes in Western Australia. The question is asked whether new housing portrayed in the popular press in Western Australia considers the older and potentially frail home occupant. The publicity given to new homes over the recent past in the 'New Homes' weekly supplement of the West Australian Newspaper was reviewed and analysed to determine what emphasis has been given to ageing at home. The analysis shows that there is almost no consideration of the older, frail occupant in the design of new houses. This indicates that baby-boomer consumers are not yet recognizing their own future needs of the housing market. In addition housing designers are taking no initiatives in this area.